The Effect of Attribute Framing and Justification on Capital Budgeting Decisions - Umma, Ianna; Sri Handayani, R. R. (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
This study aims to analyze the effect of the attribute framing and justification on decision making through the capital budgeting process. This study also aims to examine the effect of justification as moderation on the effect of attribute framing on capital budgeting decisions. The capital budgeting decision in this study is a decision toward the proposed capital budgeting project in the form of approving or rejecting the proposed project. This study uses a quasi-experimental research design with the data taken is primary data. The quasi-experimental research was designed 2 x 2 between subjects which was conducted to 83 financialÂ students in the Magister of Management, Diponegoro University. Data analysis techniques used in this study were one-way ANOVA and two-way ANOVA.The results of the study shows that attribute framing and justification can influence decision making through the capital budgeting process. In particular, the information that is positively presented has an impact in the higher approval of a proposed capital budgeting project. This research also concluded that justification could not reduce the effect of the attribute framing on capital budgeting decisions. This shows that belief revision theory- foundation approach cannot explain the phenomenon of this study.